Press Address to the April 2016 War. - Avanesyan, Iskuhi (History and Culture, 2025)
The April 2016 war also known as the four-day war was a large-scale military action between the Defense Army of the Republic of Artsakh and the armed forces of the Republic of Azerbaijan along the entire Artsakh-Azerbaijan line of contact. The four-day fighting prevented a full-scale war in the short term and failed Baku's plans to break the bargaining process and gain leverage to force decisions. This article presents the coverage of the April 2016 war by the news media of the conflicting parties and the international information field. The April War once again showed the importance of the media in covering the war effort.  It is noteworthy that Armenian media were able to carry out coordinated work, which prevented from causing panic and fear in the Armenian society. The Azerbaijani side emphasized the role of media in information actions accompanying the armed clashes. The proof of this was the number and nature of materials placed in Azerbaijani media during the days of war, which presented the course of events from the Azerbaijani point of view. It was noticeable that the efforts of Azerbaijani press in propaganda work and disinformation, which did not give the expected result.   The aggression unleashed by Azerbaijan indirectly contributed to the fact that also thanks to the international media the Nagorno-Karabakh Republic became the center of attention of the international community.